Peningkatan Proses Pembelajaran Tematik Terpadu Menggunakan Model Make a Match Di Kelas IV SD - Tiara Anesti; Hamimah Hamimah (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2022)
This Studyaims to describe the improvement of the process of integrated thematic learning with model cooperative type make a match in class IV elementary School 10 Bandar Create city of Padang. The type of research is the class Action study (PTK) using a qualitative and quantitative approach. The subjects in this study were teachers (researchers) and students amounted to 31 people. The study carried out two cycles. The Results of the study on the I cycle IN RPP Assessment gained an average of 81.25% (b) and increased 87.5% (b) in CYCLE II. At the teacher activity cycle I with an average of 79.68% (C) and increased by 87.5% (B) in Cycle II. While the activity of student cycle I gained an average value of 79.68% (C) and increased by 87.5% (B) in Cycle II. Thus, it can be concluded that the make a match type Cooperative model can enhance the integrated thematic learning process in Primary school.